Iain Stewart Receives 2013 Athelstan Spilhaus Award: Citation. Issue 2 (14th January 2014) - Wright, Tim
<x xml:space="preserve">Abstract</x> It is a great pleasure and an honor to give the citation for the 2013 Athelstan Spilhaus awardee, Iain Stewart, professor of geoscience communication at the University of Plymouth, recognizing his truly exceptional work over the last decade in communicating geoscience to the general public. Iain has been making documentaries for the BBC, National Geographic, and Discovery for nearly a decade. These programs have huge international audiences and wide‐reaching impact.